Current controversies on the role of behavior therapy in Tourette Syndrome - Scahill, Lawrence (Mov Disord, 2013)
Comprehensive Behavioral Intervention for Tics (CBIT) is a safe and effective treatment for managing the tics of TS. In contrast to most current medications used for the treatment of tics, the efficacy of CBIT has been demonstrated in two relatively large, multisite trials. It also shows durability of benefit over time. Similar to psychopharmacological intervention, skilled practitioners are required to implement the intervention. Despite concerns about the effort required to participate in CBIT, patients with TS and parents of children with TS appear willing to meet the requirements of the CBIT program. Efforts are underway to increase the number of trained CBIT providers in the United States. Based on available evidence, recent published guidelines suggest that CBIT can be considered a first-line treatment for persons with a tic disorders.